Konteks Transformasi Digital di Sektor Usaha Kesehatan - Dameria, Kurniati; Jane, Orpha (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Digital transformation in the health business sector, especially in hospitals, is becoming increasingly important in improving efficiency and quality of service. This paper aims to understand the role of digital transformation drivers that have changed the fundamentals of company operations and interactions with customers, especially in the health business sector and whether these driving factors are in line with those conveyed by previous research. In order to approach this problem, the author conducted a literature review of various review articles. The databases used include Emerald Insight, Google Scholar, Proquest, and Sciencedirect with a period of 5 (five) years, 17 journals were selected with the keywords "digital transformation", "hospital", and "digital hospital". This study concludes that there are internal and external factors in digital transformation, especially in the health sector, and emphasizes the role of management in implementing change. The internal and external driving factors of digital transformation are in line with a study by Ismail, Khater, and Zaki (2017) which explored the concept, nature and process of digital transformation, with a focus on strategic aspects.